‘I will show the man pepper’: Factors underlying male spousal abuse in Lagos metropolis - Chukwuma, Ifeanyi U. (International review of victimology, 2025)
Existing studies on spousal abuse have privileged women as victims while treating men as perpetrators. In Nigeria, knowledge on spousal abuse against men is very limited. Drawing from the chivalry hypothesis and women liberation theory, our study used qualitative data derived from the conduct of 12 in-depth interviews with male victims, 4 focus groups with married men and women and 6 key-informant interviews conducted with lawyers, police officers, and religious leaders in Lagos Metropolis to examine the factors responsible for spousal violence against men. Results indicate that spousal abuse against men is prevalent in Lagos State. However, cases are often unreported by victims and seldom covered by the media. The factors responsible include a history of family violence, financial difficulties, a history of violence while dating, and deprivation of time and affection. Policy implications, particularly the need for the media to be more responsive, are discussed.